Estudo das propriedades dielétricas e magnéticas da matriz compósita: SrBi2Nb2O9(SBN)X-BaFe12O9(BFO)1-X - Theophilo, Klara Rhaissa Burlamaqui (2011)
In this work we studied the properties of composites based in M-type barium hexaferrites BFO (BaFe12O19) and ferroelectric ceramic SBN (SrBi2Nb2O9). M-type barium hexaferrites (BaFe12O19) come out as a new alternative for the low cost production of ferrofluids, magnetic record media and sensors. Some of its characteristics are high magnetic saturation, high coercivity and good resistance to corrosion. Besides, the SBN (SrBi2Nb2O9) is a ceramic with uncountable applications in devices where ferro-piezoeletrics materials are needed. This material shows a good fatigue resistance, being one of the most liable substitutes for the Lead Zirconate Titanate (PZT) in the ferroelectrics random access memory (FERAM). The magneto-dielectric matrix composite (SrBi2Nb2O9)x(BaFe12O19)100-x, where x stands for 0,25,50,75 and 100 wt% were prepared by a new procedure in the solid state route. Also, it was done a study in the effects of a group of organic (TEOS, PVA and glycerin) binders in the structural properties of the ceramic matrix composites. The composite was analyzed with X-ray diffraction, Raman and Infrared spectroscopy, Mössbauer spectroscopy and scanning electron microscope (SEM) for a better understanding of the microstructural properties. Radiofrequency (RF) dielectric measurements and Impedance analysis, magnetic and electric hysteresis loops, microwave dielectric measures and monopole antenna measures and simulation are discussed as well.